2023
DOI: 10.1590/s1677-5538.ibju.2023.0060
|View full text |Cite
|
Sign up to set email alerts
|

Is it necessary for all patients with suspicious lesions undergo systematic biopsy in the era of MRI-TRUS fusion targeted biopsy?

Abstract: Purpose Targeted biopsy (TB) combined with systematic biopsy (SB) is an optimized mode of prostate biopsy but can often lead to oversampling and overdiagnosis accompanied by potential biopsy-related complications and patient discomfort. Here, we attempted to reasonably stratify the patient population based on multi-parameter indicators with the aim of avoiding unnecessary SB. Methods In total, 340 biopsy-naïve men with suspected lesions, prostate-specific antigen (PSA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…In the quest to determine the best protocol for performing targeted prostate biopsies using fusion images from MRI for the most accurate diagnosis and the lowest aggressiveness, several series have been published with multiple biopsy protocols. These include sampling only in the peripheral prostate area, avoiding transition zone biopsy ( 31 ), performing saturation biopsies in the target area ( 32 ), combine PSA D and PI-RADS to exclusively conduct target biopsies in patients with elevated PSA D, eliminating the need for systematic biopsies ( 33 ), using Umbra (targeted lesion) and Penumbra (perilesional) samples ( 34 ), optimizing the number of cores by obtaining only three or fewer core samples per targeted lesion ( 35 ), or conducting only biopsy samples in the target lesion without systematic biopsies ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the quest to determine the best protocol for performing targeted prostate biopsies using fusion images from MRI for the most accurate diagnosis and the lowest aggressiveness, several series have been published with multiple biopsy protocols. These include sampling only in the peripheral prostate area, avoiding transition zone biopsy ( 31 ), performing saturation biopsies in the target area ( 32 ), combine PSA D and PI-RADS to exclusively conduct target biopsies in patients with elevated PSA D, eliminating the need for systematic biopsies ( 33 ), using Umbra (targeted lesion) and Penumbra (perilesional) samples ( 34 ), optimizing the number of cores by obtaining only three or fewer core samples per targeted lesion ( 35 ), or conducting only biopsy samples in the target lesion without systematic biopsies ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of PSAD and mpMRI has been investigated ( 4 - 9 , 23 , 29 , 30 ). Pagniez et al performed systematic review (16 studies) and meta-analyses (8 studies with 1,015 patients) and concluded that PSAD <0.15ng/mL2 in the presence of negative mpMRI was the most useful factor to identify males without CSPCa who could avoid PBx.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of the prostate with mpMRI has become increasingly valuable in prostate cancer management as image quality has improved with advancements like high-field strength magnets. For initial management, mpMRI is particularly useful for improving detection of clinically significant prostate cancer and guiding both transrectal and transperineal targeted biopsies ( 11 - 13 ). Although mpMRI is not yet integrated in guidelines for preoperative planning, mpMRI findings are likely to influence the surgical plan especially in high-risk tumors ( 14 ).…”
Section: Discussionmentioning
confidence: 99%